Effects of aerobic exercise training on sympathetic and renal responses to mental stress in humans - Ray, Chester A. (American Physiological Society, 2010)
The effects of aerobic exercise training (ET) on muscle sympathetic nerve activity (MSNA) and renal vascular responses to mental stress (MS) have not been determined in humans. We hypothesized that aerobic ET would reduce MSNA and renal vasoconstriction during MS. MSNA, mean arterial pressure (MAP), heart rate, renal blood flow velocity (RBFV), and peak oxygen uptake (V̇o(2 peak)) were recorded in 23 healthy adults. Fourteen subjects participated in 8 wk of aerobic ET, while nine subjects served as sedentary controls (Con). ET significantly increased V̇o(2 peak) (Δ18 ± 1%; P < 0.001) and decreased RBFV at rest (60 ± 4 to 48 ± 3 cm/s; P < 0.01), whereas Con did not alter V̇o(2 peak) or RBFV. ET did not alter resting MSNA (11 ± 1 to 9 ± 1 bursts/min) or MAP (84 ± 2 to 83 ± 2 mmHg), and these findings were similar in the Con group. MS elicited similar increases in MSNA (∼Δ2 bursts/min; P < 0.05), MAP (∼Δ15 mmHg; P < 0.001), and heart rate (∼Δ20 beats/min; P < 0.001) before and after ET, and the responses were not different between ET and Con. Likewise, MS elicited similar decreases in RBFV and renal vascular conductance before and after ET, and the responses were not different between ET and Con. Perceived stress levels during MS were similar before and after the 8-wk study in both ET and Con. In conclusion, ET does not alter MSNA and renal vascular responses to MS in healthy humans.